Graphene Substrates Promote the Differentiation of Inner Ear Lgr5+ Progenitor Cells Into Hair Cells - Ding, Xiaoqiong; Hu, Yangnan; Cheng, Hong; Zhang, Xiaoli; Lu, Ling; Gao, Song; Cheng, Cheng; Wang, Lifen; Qian, Xiaoyun; Zhang, Chen; Chai, Renjie; Gao, Xia; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The ideal treatment for sensory hearing loss is to regenerate inner ear hair cells (HCs) through stem cell therapy, thereby restoring the function and structure of the cochlea. Previous studies have found that Lgr5+ supporting cells (SCs) in the inner ear can regenerate HCs, thus being considered inner ear progenitor cells. In addition to traditional biochemical factors, physical factors such as electrical conductivity also play a crucial role in the regulation of stem cell proliferation and differentiation. In this study, the graphene substrates were used to culture Lgr5+ progenitor cells and investigated their regulatory effects on cells. It was demonstrated that the graphene substrates displayed great cytocompatibility for Lgr5+ progenitors and promoted their sphere-forming ability. Moreover, more Myosin7a+ cells were found on the graphene substrates compared with tissue culture polystyrene (TCPS). These results suggest that graphene is an efficient interface that can promote the differentiation of Lgr5+ progenitors into HCs, which is great significance for its future application in combination with Lgr5+ cells to regenerate HCs in the inner ear.